NATIONALISM AND RASHTRIYA SWAYAMSEVAK SANGH IN THE POST-INDEPENDENCE PERIOD: स्वातंत्र्योत्तर काल में राष्ट्रवाद एवं राष्ट्रीय स्वयं सेवक संघ - Pandey, Preeti (International Journal of Research -GRANTHAALAYAH, 2021)
English: Nationalism is a subject in which there has been controversy from time to time. When it comes to Rashtriya Swayamsevak Sangh, there are often misconceptions that it opposes nationalism, but this is a myth. For this purpose, this letter has been written with special reference to the post-independence period. Writing this letter is very relevant at present because even today many people do not know the true nature of this organization and are keeping distance due to this. We find that if understood in the context of proper evidence, then this organization is also a socio-cultural organization like other organizations, which since its inception in 1925 till today is determined towards social upliftment and national upliftment. Discipline is its main weapon. It means that the Rashtriya Swayamsevak Sangh cooperated with the government in resolving the problems that arose after independence, although it was banned but again proved to be immaculate and moved forward in the forward responsibility with great energy. For this research, The subject has been reviewed in the then circumstances by studying books, newspapers related to Golwalkar ji and related to nationalism. Hindi: स्वातंत्र्योत्तर काल में राष्ट्रवाद की भावना पर प्रायः प्रश्नचिन्ह लगाये जाते रहे हैं क्योंकि सबका मानना है कि स्वतंत्रता प्राप्त होते ही राष्ट्रवाद की आवश्यकता की पूर्ति हो जाती है किन्तु यह एक भ्रामक चिन्तन है। राष्ट्र के प्रति, प्रेम, विश्वास, आस्था एवं स्वार्थ के त्याग का संयुक्त भाव है जिसका सम्बन्ध राष्ट्र के अस्तित्व से होता है। जब स्वतंत्रता आन्दोलन चल रहा था तब यह अवधारणा एक सामान्य भाव से सबके बीच में पनप रही थी एवं आवेग तथा संवेग अपने चरम पर था। उत्तर काल में इसकी गति शनैः अवश्य हो जाती है किन्तु राष्ट्रवाद की भावना का अन्त नहीं होता। इस काल में यह अवधारणा कई धाराओं में विकसित होती दिखती है। इसी में एक धारा का विकास 1925 में जन्मे संगठन राष्ट्रीय स्वंय सेवक संघ में पोषित होती है।